UNSUR ACCIDENTALIA DALAM PEMBELIAN ONLINE PRE ORDER DIKAITAN DENGAN ASAS KEBEBASAN BERKONTRAK - Yudi Kornelis (Journal of Judicial Review, 2019)
In the online purchasing pre order system is usually carried out in an agreement between the seller and the buyers, but frequently an agreement which are based on the freedom of contract principle was not pay attention to elements that should appear in an agreement, which are elements of accidentalia. The method used in this research is descriptive analytical through a normative approach based on applicable law principles, concepts and norm and law theories related to juridical facts that is relevant with the analyzed legal issue. The result of this research it can be concluded that the failure to apply the accidentalia element in online agreement pre order led to the birth of a exemption clause that could harm either party, but with the principle of freedom of contract agreements with standard clauses basically not prohibited by law for a seller that outlines the terms in accordance with they wishes as outlined in the agreement such standard does not violate morality, public order and violate laws and forms of legal protection for the injured party by performing the compensation payment to be paid by the seller to the buyer resulting from errors.